2008
DOI: 10.1073/pnas.0804438105
|View full text |Cite
|
Sign up to set email alerts
|

A microRNA signature for a BMP2-induced osteoblast lineage commitment program

Abstract: Bone morphogenetic proteins (BMPs) are potent morphogens that activate transcriptional programs for lineage determination. How BMP induction of a phenotype is coordinated with microRNAs (miRNAs) that inhibit biological pathways to control cell differentiation, remains unknown. Here, we show by profiling miRNAs during BMP2 induced osteogenesis of C2C12 mesenchymal cells, that 22 of 25 miRNAs which significantly changed in response to BMP2 are down-regulated. These miRNAs are each predicted to target components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
443
1
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 510 publications
(474 citation statements)
references
References 34 publications
20
443
1
10
Order By: Relevance
“…(27) miR-133 and miR-135 functionally inhibit differentiation of osteoprogenitors by attenuating Runx2 and Smad5 activities that synergistically contribute to bone formation. (28) miR-204/ 211 acts as negative regulators of osteoblast differentiation and subsequent mineralization in mesenchymal progenitor cells and bone marrow stromal cells through a negative regulation of Runx2 protein translation. (15) All these miRNAs directly target osteoblast differentiation factors.…”
Section: Discussionmentioning
confidence: 99%
“…(27) miR-133 and miR-135 functionally inhibit differentiation of osteoprogenitors by attenuating Runx2 and Smad5 activities that synergistically contribute to bone formation. (28) miR-204/ 211 acts as negative regulators of osteoblast differentiation and subsequent mineralization in mesenchymal progenitor cells and bone marrow stromal cells through a negative regulation of Runx2 protein translation. (15) All these miRNAs directly target osteoblast differentiation factors.…”
Section: Discussionmentioning
confidence: 99%
“…(13,(30)(31)(32) Cells were stimulated with BMP2 in serumfree medium, and the involvement of JNK1 in regulating osteoblastic differentiation was investigated. We found that under such conditions, BMP2 induced ALP activity and JNK inhibition increased it similar to the results in serum-containing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In human adipose tissue-derived MSCs (hADSCs), miR-26a has been reported to repress the translation of the osteogenic marker, SMAD1 (15), whereas overexpression of miR-196a regulates HOXC8, enhances osteogenic differentiation, and decreases hADSC proliferation (16). miR-125b has been shown to inhibit osteoblast differentiation in the mouse MSC line ST2 (17), whereas miR-133 and -135 directly target Runx2 and Smad5, respectively, and inhibit differentiation of osteoprogenitors of C2C12 mesenchymal cells (18). Moreover, miR-141 and -200a were recently found to be involved in preosteoblast differentiation through regulation of their common target Dlx5 (19), whereas miR-206 inhibits osteogenesis in vitro and in vivo by targeting Cx43 (20).…”
mentioning
confidence: 99%